Answer: Option B
She should use the fact that the
opposite sides of a parallelogram are
congruent and then use the
Pythagorean theorem.
We cannot use the diagonals of square property because this is a rectangle, opposite angles will also not work, and we cannot use the diagonal property because thats what we have to prove.
Must click thanks and mark brainliest
Answer:
<h2 /><h2>
<em><u>an</u></em><em><u>swer</u></em><em><u> will</u></em><em><u> be</u></em><em> </em><em>5</em><em>2</em><em>5</em><em>0</em></h2>
<em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em><em>-</em>
<em>
</em>
Answer:
8+12f
hope this helps
have a good day :)
Step-by-step explanation:
Answer: y=0,5x²-x-1,5.
Step-by-step explanation:
![(-1;0)\ \ \ \ (3;0)\ \ \ \ (1;-2) \ \ \ \ y=ax^2+bx+c\ ?\\\left\{\begin{array}{ccc}a*(-1)^2+b*(-1)+c=0\\a*3^2+b*3+c=0\\a*1^2+b*1+c=-2\end{array}\right \ \ \ \ \ \left\{\begin{array}{ccc}a-b+c=0\ \ (1)\\9a+3b+c=0\ (2)\\a+b+c=-2\ (3)\end{array}\right \\](https://tex.z-dn.net/?f=%28-1%3B0%29%5C%20%5C%20%5C%20%5C%20%283%3B0%29%5C%20%5C%20%5C%20%5C%20%281%3B-2%29%20%20%20%5C%20%5C%20%5C%20%5C%20%20y%3Dax%5E2%2Bbx%2Bc%5C%20%3F%5C%5C%5Cleft%5C%7B%5Cbegin%7Barray%7D%7Bccc%7Da%2A%28-1%29%5E2%2Bb%2A%28-1%29%2Bc%3D0%5C%5Ca%2A3%5E2%2Bb%2A3%2Bc%3D0%5C%5Ca%2A1%5E2%2Bb%2A1%2Bc%3D-2%5Cend%7Barray%7D%5Cright%20%5C%20%5C%20%5C%20%5C%20%20%5C%20%5Cleft%5C%7B%5Cbegin%7Barray%7D%7Bccc%7Da-b%2Bc%3D0%5C%20%5C%20%281%29%5C%5C9a%2B3b%2Bc%3D0%5C%20%282%29%5C%5Ca%2Bb%2Bc%3D-2%5C%20%283%29%5Cend%7Barray%7D%5Cright%20%20%5C%5C)
We summarize (1) and (3):
![2a+2c=-2\ |:2\\a+c=-1\ \ \ \ \Rightarrow\\a+b+c=-2\\(a+s)+b=-2\\-1+b=-2\\b=-1.](https://tex.z-dn.net/?f=2a%2B2c%3D-2%5C%20%7C%3A2%5C%5Ca%2Bc%3D-1%5C%20%5C%20%5C%20%5C%20%5CRightarrow%5C%5Ca%2Bb%2Bc%3D-2%5C%5C%28a%2Bs%29%2Bb%3D-2%5C%5C-1%2Bb%3D-2%5C%5Cb%3D-1.)
Substitute b=-1 into (2):
![9a+3*(-1)+c=0\\9a-3+c=0\\9a+c=3\ \ (5).\\](https://tex.z-dn.net/?f=9a%2B3%2A%28-1%29%2Bc%3D0%5C%5C9a-3%2Bc%3D0%5C%5C9a%2Bc%3D3%5C%20%5C%20%285%29.%5C%5C)
From (5) subtract (4):
![8a=4\ |:8\\a=0,5.\ \ \ \ \Rightarrow\\](https://tex.z-dn.net/?f=8a%3D4%5C%20%7C%3A8%5C%5Ca%3D0%2C5.%5C%20%5C%20%5C%20%5C%20%20%5CRightarrow%5C%5C)
Substitute a=0,5 into (4):
![0,5+c=-1\\c=-1,5.](https://tex.z-dn.net/?f=0%2C5%2Bc%3D-1%5C%5Cc%3D-1%2C5.)
Hense:
y=0,5x²-x-1,5.